Volatile compounds of olive oils from different geographic regions in Turkey - Şeyma Şişik Oğraş; Güzin Kaban; Mükerrem Kaya (International Journal of Food Properties, 2018)
In this research, changes in volatile compounds of olive oil were investigated in terms of cultivar, harvest year, and geographic regions (Mediterranean, Aegean, Southeastern Anatolia, Marmara, and Black Sea) were investigated. Volatile compounds of olive oils were extracted by using solid-phase microextraction (SPME) method and were identified with gas chromatography–mass spectrometry. A total of 59 volatile compounds from seven different chemical groups including aldehydes, ketones, hydrocarbons, alcohols, esters, terpenes, and furans were identified. Aldehydes were detected as the major group in all geographic regions. Among aldehydes, trans-2-hexenal was found to be relatively higher. Alcohols and esters were determined as other important compounds. While many volatile compounds were affected by olive cultivar factor, this factor had no significant effect on esters. Principal component analysis showed that volatile compounds could play an important role in the separation of regions.